85PValidation and implementation of a bespoke pan-cancer NGS panel for FFPE solid tumour analysis within an NHS setting. (7th November 2019) - Roberts, H; Wood, S; McNeil, E; White, R; Morgan, S
Abstract: Background: The All Wales Medical Genomics Service (AWMGS) receives around 90 FFPE solid tumour samples per week for genetic analysis. Streamlining of testing is required in order to ensure the laboratory has the capacity and capability to meet the growing needs of the precision medicine era. With this in mind, AWMGS aimed to validate and incorporate a single NGS panel into service for the detection of, in the first instance, single nucleotide variations in a range of tumour types using a minimum of 10ng FFPE-derived DNA. Methods: The validation involved the evaluation of the panel for the detection of single nucleotide variations in FFPE-extracted DNA. The workflow consisted of a SeqCap EZ HyperCap (Roche) protocol, sequencing on the Nextseq 550 (Illumina) and an in-house bioinformatic analysis pipeline. The validation encompassed the determination of assay sensitivity, specificity, accuracy, reproducibility and limit of detection via a series of validation rounds whereby previously tested surplus FFPE-derived DNAs of known genotype along with 2 cell-line reference standards were used as control samples to evaluate the performance of the panel. Results: The panel showed a high degree of specificity, sensitivity and reproducibility, and could reliably detect variants in samples with as little as 10ng input DNA. However, despite multiple optimisation attempts, low input samples of < 50ng DNA did not consistently achieve the 250x read depth required to ensure a 5% variant could be excluded with confidence. Conclusions: AWMGS successfully validated and optimised a bespoke NGS pan-cancer panel to provide molecular characterisation of FFPE solid tumour samples, with a minimum requirement of 50ng input DNA. This panel was implemented into the laboratory in a phased approach, initially replacing existing technologies for the delivery of existing NHS services. The panel provides an increased level of genomic information compared to previous testing methods and has greater clinical utility. As the panel has been designed to detect copy number and structural variations, once validated within the laboratory, this will have an even greater impact on the streamlining of testing. Legal entity responsible for the study: Cardiff and Vale University Health Board. Funding: NHS England's Estates and Technology Transformation Fund. Disclosure: All authors have declared no conflicts of interest.